Water Uptake Tradeoffs of Dominant Shrub Species in the Coastal Wetlands of the Yellow River Delta, China - Jinfang Zhu; Jingtao Liu; Junsheng Li; Caiyun Zhao; Jingkuan Sun (Frontiers in Plant Science, 2022)
Tamarix chinensis and Ziziphus jujuba are two dominant shrub species on Chenier Island in the Yellow River Delta, China. Water is a restrictive factor determining the plant growth, vegetation composition, and community succession in this coastal zone. We investigated how water uptake tradeoffs of the two shrub species responded to soil water fluctuations caused by seasonal variations of precipitation. The soil water content, salinity and δ18O values of potential water sources (soil water in 0–20, 20–40, 40–60, and 60–100 cm soil layers, and groundwater) and plant xylem water were measured in wet (July 2013) and dry (July 2014) seasons. The IsoSource model was employed to calculate the contributions of different water sources to plant xylem water. The results showed that δ18O values of soil water decreased significantly with soil depth in the dry season, while increased significantly with soil depth in the wet season. In the wet season, when the soil water was abundant, Z. jujuba mostly used the soil water from the 60–100 cm layer, while T. chinensis took up a mixture of groundwater and soil water from the 60–100 cm layer. In the dry season, when the soil water was depleted because of low precipitation, Z. jujuba mainly took up a mixture of the soil water from 20 to 100 cm soil layers, while T. chinensis mainly used groundwater. T. chinensis and Z. jujuba showed different ecological amplitudes of water sources during dry and wet seasons. The niche differentiation of major water sources for T. chinensis and Z. jujuba demonstrated their adaptabilities to the fluctuations of soil moisture in water-limited ecosystems. Water niche differentiations of coexisting shrub species were expected to minimize their competition for limited water sources, contributing to successful coexistence and increasing the resilience of the coastal wetland ecosystem to drought.